2013
DOI: 10.1007/s13593-013-0168-3
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen fertilization impacts biocontrol of tomato gray mold

Abstract: Gray mold, caused by Botrytis cinerea, is a common threat for greenhouse production of tomatoes. Control of this disease can be difficult even with chemical treatments, and alternative methods are needed. Nitrogen (N) fertilization is known to modify the impact of pathogens on plants. However, there is scarce knowledge about the effect of fertilization on the efficacy of biocontrol. Here, we studied the effect of N fertilization on biocontrol agents Trichoderma atroviride and Microdochium dimerum that protect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…Even applied on plants together with biological control agents, chitosan enhanced the efficacy in the control of pathogens [144,145]. Soil amendment with chitosan has frequently been shown to control Fusarium wilts [90,146,147] and gray molds [97,103] in a number of crops.…”
Section: Chitosan In Crop Production and Protectionmentioning
confidence: 99%
“…Even applied on plants together with biological control agents, chitosan enhanced the efficacy in the control of pathogens [144,145]. Soil amendment with chitosan has frequently been shown to control Fusarium wilts [90,146,147] and gray molds [97,103] in a number of crops.…”
Section: Chitosan In Crop Production and Protectionmentioning
confidence: 99%
“…Lots of studies showed that chitosan is not only an antimicrobial agent but also an effective elicitor of plant systemic acquired resistance to pathogens (Table 3). Even applied on plants together with the biological control agents, chitosan enhanced the efficacy in the control of pathogens (Vallance et al 2011;Abro et al 2013). It is possible for chitosan as a new type of green pesticides to play an important role in agriculture owing to its nontoxic, biodegradable, and nonpollution characteristics.…”
Section: Elicitation Of Plant Defense Responses By Chitosanmentioning
confidence: 99%
“…On the other hand, some natural products have undergone research, such as (poly-D-glucosamine) and plant-origin oligosaccharides; they have the ability to elicit defense responses and/or induce protection against B. cinerea in tomatoes and other crops or vegetables [ 15 18 ]. Meanwhile, Abro et al [ 19 ] reported that nitrogen (N) fertilization had the ability to strengthen the control efficacy of the biocontrol agents (BCAs) Trichoderma atroviride and Microdochium dimerum . Although N fertilization was a promising method to control tomato gray mold, the key was BCAs.…”
Section: Introductionmentioning
confidence: 99%
“…Biological control of B. cinerea has been broadly researched [ 19 28 ]. Research has shown that the marine yeast Rhodosporidium paludigenum has a significant control efficacy in postharvest tomato fruits via nutrient competition.…”
Section: Introductionmentioning
confidence: 99%